The Role of Adjuvant Hormonal Treatment after Surgery for Localized High-Risk Prostate Cancer: Results of a Matched Multiinstitutional Analysis. (31st January 2012) - Schubert, Maria; Joniau, Steven; Gontero, Paolo; Kneitz, Susanne; Scholz, Claus-Jü rgen; Kneitz, Burkhard; Briganti, Alberto; Karnes, R. Jeffrey; Tombal, Bertrand; Walz, Jochen; Hsu, Chao-Yu; Marchioro, Giansilvio; et al.
Abstract : Introduction . To assess the role of adjuvant androgen deprivation therapy (ADT) in high-risk prostate cancer patients (PCa) after surgery. Materials and Methods. The analysis case matched 172 high-risk PCa patients with positive section margins or non-organ confined disease and negative lymph nodes to receive adjuvant ADT (group 1, n = 86 ) or no adjuvant ADT (group 2, n = 86 ). Results . Only 11.6% of the patients died, 2.3% PCa related. Estimated 5–10-year clinical progression-free survival was 96.9% (94.3%) for group 1 and 73.7% (67.0%) for group 2, respectively. Subgroup analysis identified men with T2/T3a tumors at low-risk and T3b margins positive disease at higher risk for progression. Conclusion . Patients with T2/T3a tumors are at low-risk for metastatic disease and cancer-related death and do not need adjuvant ADT. We identified men with T3b margin positive disease at highest risk for clinical progression. These patients benefit from immediate adjuvant ADT.